Perbedaan kadar oksigen serebral (RSO2) pada penggunaan sevofluran dan isofluran sebagai anestesi inhalasi dengan pengukuran Near Infrared Spectroscopy (NIRS) pada pasien laparatomi - Rian Army; Yutu Solihat; Andriamuri P. Lubis; Rina Amelia (Poltekkes Kemenkes Aceh, 2023)
Background: Changes in cerebral oxygen are due to the effect of inhalation anesthesia on cerebral blood flow, which can reduce cerebral oxygenation if cerebral blood flow decreases. This study aims to analyze the difference in cerebral oxygen levels in sevoflurane compared to isoflurane as an inhalation anesthetic.Objective: The study aims to analyze the difference in cerebral oxygen levels in using sevoflurane versus isoflurane as an inhalation anesthetic.Methods: This study is a double blind Randomized Controlled Clinical Trial. This study was conducted at Haji Adam Malik Hospital Medan. This study was conducted in August 2022. The research sample was patients with Laparotomy surgery at the Haji Adam Malik Medan Central General Hospital who met the research criteria. The number of subjects who met the inclusion criteria was 26 patients, with 13 patients in the group receiving sevoflurane and 13 patients receiving isoflurane. Data to be collected were analyzed with statistic-independent T-test and Mann-Whitney.Results: Of the 26 patients 13 patients in the group received sevoflurane, and 13 patients in the group received isoflurane. Furthermore, the two groups were randomized to obtain a balanced group of 13 patients per group. In this study, it was found that the cerebral saturation value of rSO2 in the sevoflurane group before induction (T) compared to 5 minutes after induction (T1) or after surgery (T2) showed no statistically significant difference, while the cerebral saturation value of rSO2 in the isoflurane group there was a significant change in rSO2 value (p<0,05) before induction (T) compared to 5 minutes after induction (T1) or after surgery (T2). In this study, it was found that the comparison of the rSO2 values of the sevoflurane and isoflurane groups showed significant differences at the time of examination of the rSO2 value 5 minutes after induction (T1) and after surgery (T2).Conclusion: The role of sevoflurane as an inhalation drug in Laparotomy surgery is more to maintain cerebral oxygenation than isoflurane, as indicated by the rSO2 value on NIRS, which does not have a significant decrease for surgery.